2013
DOI: 10.1002/2013je004376
|View full text |Cite
|
Sign up to set email alerts
|

Compositional heterogeneity of central peaks within the South Pole‐Aitken Basin

Abstract: [1] Using high-spectral and -spatial resolution Moon Mineralogy Mapper data, we investigate compositional variations across the central peak structures of four impact craters within the South Pole-Aitken Basin (SPA). Two distinct causes of spectral diversity are observed. Spectral variations across the central peaks of Bhabha, Finsen, and Lyman are dominated by soil development, including the effects of space weathering and mixing with local materials. For these craters, the central peak structure is homogeneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 58 publications
5
41
0
Order By: Relevance
“…Vaughan and Head [] suggested that the stratigraphy of the SPA impact melt was differentiated into norite, LCP‐rich pyroxenite, and dunite layers from top to bottom. They suggested that the modeled stratigraphy is consistent with the rock types of central peaks observed in previous studies [ Tompkins and Pieters , ; Nakamura et al , ; Moriarty et al , ; Yamamoto et al , ]. However, the rock type of the top layer of their estimated stratigraphy (norite, which is plagioclase‐rich lithology containing LCP) and that of our observation (HCP‐rich pyroxenite based on average FeO abundance) are inconsistent.…”
Section: Geological Interpretation and Discussionsupporting
confidence: 88%
“…Vaughan and Head [] suggested that the stratigraphy of the SPA impact melt was differentiated into norite, LCP‐rich pyroxenite, and dunite layers from top to bottom. They suggested that the modeled stratigraphy is consistent with the rock types of central peaks observed in previous studies [ Tompkins and Pieters , ; Nakamura et al , ; Moriarty et al , ; Yamamoto et al , ]. However, the rock type of the top layer of their estimated stratigraphy (norite, which is plagioclase‐rich lithology containing LCP) and that of our observation (HCP‐rich pyroxenite based on average FeO abundance) are inconsistent.…”
Section: Geological Interpretation and Discussionsupporting
confidence: 88%
“…In general, SPA materials are enriched in mafic minerals relative to the highlands feldspathic crust (e.g., Lawrence et al, ; Pieters et al, ). Across the basin, the most common nonmare mafic component appears to be Mg‐rich, low‐Ca pyroxenes (Mg‐Px) (Cahill et al, ; Klima, Pieters, et al, ; Moriarty et al, ; Nakamura et al, ; Pieters et al, ; Tompkins & Pieters, ). The pervasive nature of these Mg‐pyroxene‐rich materials across the basin suggests that they are a result of SPA formation, either as impact melt (e.g., Nakamura et al, ; Vaughan & Head, ) or excavated materials from the lower crust and/or upper mantle (Blewett et al, ; Klima, Dyar, & Pieters, ; Lucey et al, ; Moriarty & Pieters, ; Ohtake et al, ; Pieters et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Our analyses focus on the properties of this structure. Central peaks of large complex craters within SPA typically exhibit significant low-Ca pyroxene (LCP) ( Figure S2d), although some variation in pyroxene abundance and composition is observed [Tompkins and Pieters, 1999;Pieters et al, 2001;Cahill et al, 2009;Nakamura et al, 2009;Klima et al, 2011b;Moriarty et al, 2013]. Several asymmetric slopes emanate radially from the central depression: gradual, elongated slopes to the north and west and sharper slopes to the south and east.…”
Section: Introductionmentioning
confidence: 99%